BLOCK AND RANDOM TRIPTYCENE INTEGRATED POLY(ARYLENE ETHER SULFONE) FOR POLYMER ELECTROLYTE MEMBRANE APPLICATIONS. - MURUGAYA, KARTIGESAN (2024)
Due to growing concerns about the exhaustion of petroleum-based energy supplies and global change of climate, fuel cell developments have received substantial interest in recent times due to their high performance and reduced emissions. To overcome issues such as high swelling and poor proton conductivity of current PEMs, a series of triptycene integrated poly (arylene ether sulfone) (PAES), with both block and random microphase were synthesized by controlling the telechelic oligomer A and telechelic oligomer B ratio (1:2), (1:1), (2:1) via condensation polymerization for the application of polymer electrolyte membrane fuel cell (PEMFC). It was revealed that, only the ratio with (1:2) of telechelic oligomer A to telechelic oligomer B ratio portrayed filming forming properties for block copolymers. Subsequently, the random PAES copolymer was synthesized using the same oligomer ratio of (1 telechelic oligomer A: 2 telechelic oligomer B. 1HNMR, FTIR and GPC analysis confirmed the chemical structure of synthesized triptycene monomer, oligomers and polymers. While AFM images just showed variations in the surface's viscosity and adhesion qualities, a clear phase separation differences in between block and random PAES was hardly seen. Due to its free volume property, the triptycene integration into the polymer main chain results in excellent dimensional stability for block and random copolymers at both 25℃ and 80℃. Meanwhile FESEM images verified the presence of pores in the membrane which might have been attributed by triptycene, further investigation via imageJ® software reveals abundant presence of larger pores in block PAES membrane. The membranes also displayed good water uptake and ion exchange capacity which were compared with Nafion 211® from previous studies. The thermal stability studied via TGA and DMA, together with proton conductivity and fuel cell performance seem to be a promising application for PEMFC. Hence, the block copolymers outperformed random copolymers and the integration of triptycene is proven to enhance the quality of PEM.